(untitled) (Research, Society and Development, 2020)
Beta-lactam antibiotics have the same mechanism of action, the inhibition of bacterial cell wall synthesis, mainly affecting peptidoglycan. They are considered safety antibiotics, since, when they directly reach the cell wall, they cause bacterial autolysis. The objective of this research is to evaluate the affinity between the beta-lactamase enzyme and several classes of beta-lactam antibiotics. This study is a research of exploratory type methodology, of quantitative nature with application of computer simulation with application of methods with computer simulation with the evaluation of the connection scores by traditional molecular anchoring using the AutoDock 4.2 program. We identified that, in the results of molecular docking simulations, penicillin and cephalosporin showed greater affinity at the catalytic site, due to a lower Gibbs free energy. It is concluded that the affinity of the antibiotics penicillin and cephalosporin may in the future represent an obstacle for the treatment of diseases such as, mild and moderate infections of the respiratory tract, skin infections, venereal infections, and the prophylaxis of rheumatic diseases. We suggest that further studies evaluate the simulations with molecular dynamics tests to see if, considering the flexibility of the enzyme, even more accurate results would be possible.